The Effect of the Intensity of Food Purchases 0leh Free Nutritious Meal Program on the Income of Local Food MSMEs as a Source of Economic Learning in Teko Village - Nila juliana; Mispandi; Rohaeniyah zain (LP2M IAIN Palopo, 2026)
This study discusses the influence of the intensity of food purchases by the Free Nutritious Meal Program (MBG) on the income of local food MSMEs in Teko Village and its use as a source of contextual economic learning. The results of the study show that the MBG Program has a positive impact on increasing MSME income through regular and sustainable food purchases. The increase in income not only provides economic benefits for MSME actors, especially vegetable traders who are the main suppliers of food for the program, but can also be used as a source of economic learning that connects theoretical concepts with real conditions in society. Thus, the MBG Program has an important role not only in supporting the fulfillment of community nutrition, but also in improving the economic welfare of local communities and providing educational value for economic learning.